Penerapan Literasi Keuangan Dalam Memahami Financial Technology - Susi Sih Kusumawardhany; Yunita Kurnia Shanti; Khoirunnisa Azzahra; Baiq Fitri Arianti; Anggun Putri Romadhina (FEB-UP Press, 2021)
Financial Technology (Fin Tech) is a form of technology-based financial service that is developing in the world. The purpose of Financial Technology is to facilitate the transaction process between buyers and sellers and to reduce gaps or fraud in the transaction process. However, the gap of financial knowledge, especially digital financial technology, is wide and deep. Therefore the importance of financial knowledge (financial literacy) to the community is a necessity to be carried out synergistically by stakeholders including regulators, relevant ministries / government bodies, industry associations and fintech actors, financial service institutions and others. In addition to fintech products such as digital wallets that are well known to the public, an important element in the management of knowledge is to explain aspects of transparency regarding business processes and risks of fintech. Based on this phenomenon, the community service team of the University of Pamulang S1 Accounting Study Program has conducted online counseling via the zoom application for RT 03 Residents of Villa Mellia Housing, Gunung Sindur District, Bogor Regency as a concern for the importance of understanding the use of fintech in daily life in the era globalization with digital wallets with the importance of applying good financial literacy.